The impact of external uncertainty shocks on the Korean economy - Junhyong Kim (KDI Journal of Economic Policy, 2024)
In this paper, we analyze the impact of external uncertainty shocks on the Korean economy, focusing on Russian geopolitical risks and U.S. monetary policy uncertainty. We find that increases in external uncertainties negatively affect the Korean macroeconomy, with a particularly pronounced impact on sectors highly dependent on external markets. Our micro-level analysis reveals that the effects of external uncertainties on exports vary across different countries and sectors. A firm-level analysis further suggests that Russian geopolitical risks primarily impact the economy through real friction, while U.S. monetary policy uncertainty affects it through both real and financial friction. By identifying multiple transmission channels through both a macro- and a micro-level analysis, we provide a comprehensive understanding of how uncertainty affects the real economy. Our findings could offer valuable insights for policymakers when responding to rapidly changing external conditions.
Keywords: E22; E32; F44; 330; Geopolitical Risks; Uncertainty Shocks; Investment; Global trade; Open Economy; Macroeconomics